Is Centrifugation Necessary for Processing Lipoaspirate Harvested via Water-Jet Force Assisted Technique before Grafting? Evidence of Lipoaspirate Concentration With Enhanced Fat Graft Survival. Issue 4 (October 2016) - Yin, Shilu; Luan, Jie; Fu, Su; Zhuang, Qiang
Abstract : Background: Although water-jet force–assisted liposuction technique (WAL) was demonstrated to have favorable effects on fat grafting, controversy continues concerning the application of centrifugation for lipoaspirate harvested via WAL. As a controversial technique, plastic surgeons often get perplexed to the necessity of using centrifugation during fat grafting procedure. In the present study, we adopted the recommended centrifugal intensity (1200 g, 3 minutes) to process lipoaspirate and focused on the influence of centrifugation on the fate of lipoaspirate harvested with WAL technique. Methods: Lipoaspirate was obtained from 10 healthy Chinese female patients who underwent cosmetic liposuction. The harvested lipoaspirate was either not centrifuged (group A) or centrifuged at 1200 g for 3 minutes (group B). Lipoaspirate from each group was compared in the in vitro and in vivo experiments. The influence of centrifugation on lipoaspirate viability and lipoaspirate survival after grafting were evaluated. Results: The viability of the lipoaspirates was similar between equally volumetric uncentrifugal and centrifugal lipoaspirate. However, centrifugation at 1200 g for 3 minutes concentrated stromal vascular fraction cells and adipose-derived stem cells in lipoaspirate; greater angiogenesis and weight retention rates were observed in centrifugal lipoaspirate after grafting than those uncentrifugal lipoaspirate. Conclusions: Centrifugation at 1200 g for 3 minutes enhanced the survival of lipoaspirate harvested via WAL technique after grafting. Centrifugation at 1200 g for 3 minutes was recommended to process lipoaspirate harvested with water-jet force assistance before grafting.